Shaman. - Lam, Yaocheng. (2010)
The "Shaman" is a live action based public service announcement. The purpose of the public service announcement is to question the balance between mankind's modernization  and climate change. In the past decade, many east Asian countries have developed economically at an astonishing pace at the expense of the earth's climate.